12-1=4p+23

Simple and best practice solution for 12-1=4p+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-1=4p+23 equation:


Simplifying
12 + -1 = 4p + 23

Combine like terms: 12 + -1 = 11
11 = 4p + 23

Reorder the terms:
11 = 23 + 4p

Solving
11 = 23 + 4p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-4p' to each side of the equation.
11 + -4p = 23 + 4p + -4p

Combine like terms: 4p + -4p = 0
11 + -4p = 23 + 0
11 + -4p = 23

Add '-11' to each side of the equation.
11 + -11 + -4p = 23 + -11

Combine like terms: 11 + -11 = 0
0 + -4p = 23 + -11
-4p = 23 + -11

Combine like terms: 23 + -11 = 12
-4p = 12

Divide each side by '-4'.
p = -3

Simplifying
p = -3

See similar equations:

| a^3+2a^2-25a-50= | | 2(y+6)=24 | | x+10=4x+1 | | -282-(+1,017)=? | | 2y+48=8 | | M^2-6=5m | | f(x)=25x+150 | | 141-6x=30x+21 | | 28+2x=6x | | 10x+4=29 | | -4.9t^2+19.6t+58.8=0 | | 6(y-5)=-6 | | 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 | | 2(x-6)+3x=8 | | 3x+30=90 | | (x^2+2x+1)(x^2+5x+4)=0 | | y=3x/12+105 | | 18-2x=2x+2 | | (y+5)(y^2-5y+25)= | | 1+6x-3x=19 | | 3x+35=13x-56 | | 4*1/2-1/3 | | 6x+17=65+3x | | (3x+30)= | | (x+-7)(x+-7)=14x | | 2(a-2)=-(a-1)/(a-4) | | X^2(5x+3)=26x |

Equations solver categories